On a mission: Achieving distinction as a business school? - D. L. Bevelander; M. J. Page; L. F. Pitt; M. Parent (South African Journal of Business Management, 2015)
This paper investigates what business schools are saying in their mission statements and whether they provide a meaningful basis for strategic choice, distinction and differentiation from a positioning perspective; or whether they are the equivalent of "table stakes" in the MBA game - undifferentiated signals that connote legitimacy. Content analysis is undertaken of the mission statements of the Financial Times 2009 top 100 full-time MBA program offering business schools. The statements are mapped and compared in the aggregate and by quartile. We conclude that the statements are for the most part homogeneous and do not serve as a basis for differentiation. However, although achieving distinction through a mission statement may indeed be difficult, it is by no means impossible, and we suggest approaches that business school deans might adopt in an effort to make their brands stand out.
Keywords: 650